Analysis of Cultural Transmission in the Dayak Bidayuh Community on the Perspective of Social Studies Education - Mirzachaerulsyah, Edwin (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This research aims to analyze cultural transmission in the Dayak Bidayuh community in Bengkayang, West Kalimantan from the perspective of social studies education. The background is their separate existence in two countries and their history of always moving from place to place but being able to maintain their identity and cultural knowledge to this day. This research uses a qualitative approach with a case study type. Data collection uses observation, interviews and documentation studies. The results of this research show (1) the history and culture of the Dayak Bidayuh community is very dynamic starting from the history of their migration from Sungkung to spreading to various places around Jagoi, Sebujit, Bau and so on, but their cultural identity is still attached, (2) Cultural transmission is carried out through firstly, the internalization process by introducing culture to children from an early age, the role of family and society is very determining in this process, secondly through cultural transformation and inheritance where verbally or in practice this culture is then passed on according to developments over time without losing its essence and value